2016
DOI: 10.5194/piahs-373-193-2016
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of changes in flood quantiles at the gauge Neu Darchau (Elbe River) from 1875 to 2013

Abstract: Abstract. Within this investigation, we focus on a detailed analysis of the discharge data of the gauge Neu Darchau (Elbe River). The Elbe River inflows onto the North Sea. The gauge Neu Darchau is the most downstream discharge gauge of the Elbe River before it becomes an estuary. We follow the questions, whether the discharge characteristics of the Elbe River have changed over the last decades and how much common flood quantiles (i.e. 100-year flood) are affected by the latest extreme events in 2002, 2006, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The Rhine River longterm data series has helped to identify the suitability of various statistical methods for accurate estimation of individual flood parameters (Thieken et al 2014;Toonen et al 2016). Studies of the flood regimes in the Danube, Oder, Vistula, Elbe and Nemunas Rivers (Cyberski et al 2006;Blöschl et al 2013;Mudersbach et al 2017;Stonevičius et al 2017) have also considerably contributed to a better understanding of the flood regimes of European rivers. These studies have identified the causes of the floods in major European rivers, as well as their duration, dates and other characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The Rhine River longterm data series has helped to identify the suitability of various statistical methods for accurate estimation of individual flood parameters (Thieken et al 2014;Toonen et al 2016). Studies of the flood regimes in the Danube, Oder, Vistula, Elbe and Nemunas Rivers (Cyberski et al 2006;Blöschl et al 2013;Mudersbach et al 2017;Stonevičius et al 2017) have also considerably contributed to a better understanding of the flood regimes of European rivers. These studies have identified the causes of the floods in major European rivers, as well as their duration, dates and other characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…1b, c). As neither temperature nor discharge exhibited noteworthy trends in seasonality in the Elbe during this period (Markovic et al, 2013;Mudersbach et al, 2016), we interpret this seasonality change as an indicator of a change in other driving processes, possibly in the responsible organisms. While the DIN input has a constant seasonal pattern, its magnitude and composition (share of NH4-N) changed remarkably throughout the time series (Figure 2c).…”
Section: Din Retentionmentioning
confidence: 74%